Synthesis and Biological Evaluation of vicinal-Diaryl Pyrazole Ethyl Carboxylate Analogs as Antiproliferative Agent against Pancreatic Cancer - Singh, Sandeep; Sharma, Rajeev Kumar; Singh, Aishwarya; Garg, Manoj; Ramajayam, R. (Asian Journal of Chemistry, 2024)
vicinal Diaryl scaffold possessing various heterocycles displayed versatile pharmacological activities ranging from antibacterial to antiviral. Herein, the synthesis of novel vicinal diaryl pyrazole ethyl carboxylate analogs as central ring and evaluated for their antiproliferative activity against pancreatic cancer line, PANC-1. Among the synthesized 27 compounds, six compounds displayed the IC50 value for antiproliferative activity in single digit micromolar. The cytotoxicity results of the synthesized compounds especially compound 25 (IC50 = 4.8 µM) confirms that these analogs may require further investigation.